Microscopic colitis in patients with ulcerative colitis or Crohn's disease: a retrospective observational study and review of the literature. (3rd April 2018) - Wickbom, Anna; Bohr, Johan; Nyhlin, Nils; Eriksson, Anders; Lapidus, Annika; Münch, Andreas; Ung, Kjell-Arne; Vigren, Lina; Öst, Åke; Tysk, Curt; ,
Abstract: Objectives: Onset of microscopic colitis (MC) in patients with ulcerative colitis (UC) or Crohn's disease (CD), or vice versa, has been reported occasionally but the subject is not well described. We therefore report a retrospective observational study of such patients and review the literature. Methods: Forty-six Swedish gastroenterology clinics were contacted about patients with diagnoses of both inflammatory bowel disease (IBD) and MC. Publications were searched on PubMed. Results: We identified 31 patients with onset of MC after a median (range) of 20 (2–52) years after diagnosis of IBD, or vice versa; 21 UC patients developed collagenous colitis (CC) ( n = 16) or lymphocytic colitis (LC) ( n = 5); nine CD patients developed CC ( n = 5) or LC ( n = 4); one CC patient developed CD. Of the 21 UC patients, 18 had extensive disease, whereas no consistent phenotype occurred in CD. Literature review revealed 27 comprehensive case reports of patients with diagnoses of both IBD and MC. Thirteen MC patients developed IBD, of which four required colectomy. Fourteen IBD patients later developed MC. There were incomplete clinical data in 115 additional reported patients. Conclusions: Altogether 173 patients with occurrence of both IBD and MC were found. The most common finding in our patients was onset of CC in a patient with UC. Although these are likely random associations of two different disorders, MC should be considered in the patient with UC or CD if there is onset of chronic watery diarrhoea without endoscopic relapse of IBD.